Sex hormone-binding globulin promotes the osteogenic differentiation potential of equine adipose-derived stromal cells by activating the BMP signaling pathway - Irwin-Huston, Jennifer M.; Bourebaba, Lynda; Bourebaba, Nabila; Tomal, Artur; Marycz, Krzysztof (Frontiers in Endocrinology, 2024)
Musculoskeletal injuries and chronic degenerative diseases pose significant challenges in equine health, impacting performance and overall well-being. Sex Hormone-Binding Globulin (SHBG) is a glycoprotein determining the bioavailability of sex hormones in the bloodstream, and exerting critical metabolic functions, thus impacting the homeostasis of many tissues including the bone.In this study, we investigated the potential role of SHBG in promoting osteogenesis and its underlying mechanisms in a model of equine adipose-derived stromal cells (ASCs). We demonstrated that SHBG treatment enhances the expression of key osteoconductive regulators in equine ASCs CD34 + cells, suggesting its therapeutic potential for bone regeneration. Specifically, SHBG increased the cellular expression of BMP2/4, osteocalcin (OCL), alkaline phosphatase (ALP), and osteopontin (OPN), crucial factors in early osteogenesis. Furthermore, SHBG treatment maintained adequate apoptosis and enhanced autophagy during osteogenic differentiation, contributing to bone formation and remodeling. SHBG further targeted mitochondrial dynamics, and promoted the reorganization of the mitochondrial network, as well as the expression of dynamics mediators including PINK, PARKIN and MFN1, suggesting its role in adapting cells to the osteogenic milieu, with implications for osteoblast maturation and differentiation. Overall, our findings provide novel insights into SHBG's role in bone formation and suggest its potential therapeutic utility for bone regeneration in equine medicine.